Government Policy Implementation Regarding Covid-19 in Makassar - Widya Surya Cendekiana; Andi Darmawansya; Muhammad Nur Iqbal Nurdin (Golden Ratio of Law and Social Policy Review (GRLSPR), 2022)
This article discusses the policies of the targeted city local government related to Covid-19 regulations as well as policies issued by the government down to the regional level. The aim is simply to provide an overview of the situation in the areas affected by the disaster after the existence of local legal policies issued by the government in the research location. The research method used in this article is normative legal research. The results of this study describe the implementation of policies in efforts to deal with Covid-19 in Government regulations at the regional level, especially Makassar City which aims to prevent transmission of Covid-19. The implementation of local government regulations has made people aware of the importance of wearing masks, one of which is contained in the contents of the health protocol rules. The existence of policies issued by regulations is not yet an antidote to the Covid-19 virus, but this policy only prevents the spawning of Covid-19. The Covid-19 Task Force is tasked with assisting control and law enforcement against health protocol violations. The team was formed to carry out direct handling in the field in controlling and enforcing health protocol laws, especially in the Makassar City area. In order to reduce the transmission of the spread of the Covid-19 virus, the government should have policies that support each other so that it is more stringent in security and supervision during the implementation of the PSBB and it is hoped that it will patrol places more often that invite people to crowded places.